2006
DOI: 10.1002/elan.200603625
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Assemblies for Bioelectrocatalytic and Bioelectronic Applications

Abstract: This work extensively covers the use of layer-by-layer (LbL) assembly of polyelectrolytes for the transduction of catalytic and affinity events. It is demonstrated that by controlling the charge of polyelectrolytes, electrostatic interactions drive then the LbL construction of supramolecular architectures with improved performance. Particularly, by adequately charging an osmium based redox polymer, a multicofactor protein (fructose dehydrogenase) may be deposited in a favored orientation resulting in a more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Within the body of work studying Au-NP-based platforms, different linking systems interconnecting the Au-NPs at electrode interfaces have been explored. Polyelectrolytes have been employed in this capacity by Murray, Fermin, and us to create composite films featuring carboxylic-functionalized monolayer-protected clusters (MPCs) as well as several types of water-soluble Au-NPs. Some of these films, including those from our own experiments, were shown to yield enhanced voltammetric signals of simple solution redox species. , More recent studies suggest that the incorporation of Au-NPs into film assemblies consistently results in more sensitive amperometric detection of targeted analytes. Several reports , focus exclusively on developing Au-NP–film interfaces or biosensor platforms with several utilizing polymer-linked Au-NP films that specifically target the more sensitive electrochemical detection of H 2 O 2 . However, in spite of the number of reports examining electrochemical interfaces incorporating Au-NPs within polymeric matrices, few of them delve into the fundamental mechanism/understanding and control or optimization of the observed electrochemistry that is attributed to the use of Au-NPs within their strategies. Given this level of understanding, the development of highly sensitive, optimized Au-NP-based electrochemical interfaces coupled with a greater fundamental understanding of its structure–function relationships remains a study of significant value to the field.…”
Section: Introductionmentioning
confidence: 97%
“…Within the body of work studying Au-NP-based platforms, different linking systems interconnecting the Au-NPs at electrode interfaces have been explored. Polyelectrolytes have been employed in this capacity by Murray, Fermin, and us to create composite films featuring carboxylic-functionalized monolayer-protected clusters (MPCs) as well as several types of water-soluble Au-NPs. Some of these films, including those from our own experiments, were shown to yield enhanced voltammetric signals of simple solution redox species. , More recent studies suggest that the incorporation of Au-NPs into film assemblies consistently results in more sensitive amperometric detection of targeted analytes. Several reports , focus exclusively on developing Au-NP–film interfaces or biosensor platforms with several utilizing polymer-linked Au-NP films that specifically target the more sensitive electrochemical detection of H 2 O 2 . However, in spite of the number of reports examining electrochemical interfaces incorporating Au-NPs within polymeric matrices, few of them delve into the fundamental mechanism/understanding and control or optimization of the observed electrochemistry that is attributed to the use of Au-NPs within their strategies. Given this level of understanding, the development of highly sensitive, optimized Au-NP-based electrochemical interfaces coupled with a greater fundamental understanding of its structure–function relationships remains a study of significant value to the field.…”
Section: Introductionmentioning
confidence: 97%
“…FDH catalyzes the 2-electron oxidation of D-fructose to 5-keto-Dfructose. Some studies have been reported on FDH with mediators at polypyrrole matrix-modified electrode [6][7][8][9], carbon paste electrode [10], membrane mimetic layer on gold electrode [11], and layer-by-layer assembly of polyelectrolytes [12]. Furthermore, FDH has a high DET activity and several biosensors and biofuel cells based on DET reactions of FDH have been reported [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…26 Similarly, Dominguez et al, also employed the LBL technique to prepare fructose biosensors based on the PVP-Os redox polymer and FDH. 27 More recently, Antiochia et al, reported the preparation of an osmium redox polymer (poly(1-vinylimidiazole) 12 -[osmium(4,4 -dimethyl-2,2 -dipyridyl) 2 Cl 2 ] 2+/+ (PVI-Os) mediated fructose dehydrogenase biosensor by direct wiring of FDH into the PVI-Os hydrogel for the detection of fructose in fruit juices and soft drinks. 2 Finally, Hickey et al, immobilized FDH into a ferrocene-based redox polymer 3-(tetramethylferrocenyl)propyl-modified linear poly(ethylenimine) (FcMe 4 -C 3 -LPEI) to develop bioanodes for fructose as part of an enzyme cascade that catalyzed the hydrolysis of sucrose to fructose and glucose and subsequent oxidation of fructose and glucose.…”
mentioning
confidence: 99%